Middle school mischief - Yūsuf, Bāsim, 1974-; Daly-Weir, Catherine (Yūsuf, Bāsim, 1974- Magical reality of Nadia (Series), 2021)
"Nadia loves fun facts. Here are a few about her: There was a magical-and hilarious-ancient Egyptian teacher named Titi trapped in her hippo amulet until she freed him last fall. Her school is choosing a new mascot and her idea is totally going to win! She's going to kick butt writing for the school newspaper this term . . . . . . Maybe. A couple of weeks in, the newspaper is a big mess. The mascot contest is mayhem, too. (Who knew choosing a costumed character could cause such controversy?!) Then Nadia and Titi discover that the hippo amulet holds a second secret, one that's super powerful-and super scary. Too bad they have no idea how to stop it. But Nadia is on the case! If she can solve the mystery of an ancient amulet, winning the mascot contest and acing her reporter assignments should be easy . . . right?"